PENGARUH PEMBERIAN MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA ALPHA HOTEL PEKANBARU - Avdon Fikva Rananda; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research is motivated by the importance of human resource management in moving the company. In a company managing human resources properly is one way to increase employee performance. In achieving good performance, employees who have high work power are needed to anticipate the opportunities and challenges of an increasingly competitive business environment. This research was conducted at Alpha Hotel Pekanbaru, Jalan Imam Munandar No. 17, Tangkerang Utara, Kec. Bukit Raya Pekanbaru. The purpose of this study was to determine the level of employee performance at Alpha Hotel Pekanbaru. The research sample was taken as many as 76 respondents but due to the impact of Covid19, the researcher only obtained 36 respondents using the census method. In this research, the methods used are descriptive and quantitative. The data obtained from interviews and distributing questionnaires were then tested with statistics through the SPSS program. The analytical method used in this research is simple and multiple regression analysis, and by going through the validity test and reliability test. In this study the results obtained are that Employee Motivation has a positive and significant effect on Employee Performance, Work Environment has a positive and significant effect on Employee Performance and Motivation and Work Environment has a positive and significant effect on Employee Performance at Alpha Hotel Pekanbaru. Keywords: Motivation, Work Environment, and Employee Performance